Nerve and Vascular Biomarkers in Skin Biopsies Differentiate Painful From Painless Peripheral Neuropathy in Type 2 Diabetes - Shillo, Pallai; Yiangou, Yiangos; Donatien, Philippe; Greig, Marni; Selvarajah, Dinesh; Wilkinson, Iain D.; Anand, Praveen; Tesfaye, Solomon (Frontiers in Pain Research, 2021)
Painful diabetic peripheral neuropathy can be intractable with a major impact, yet the underlying pain mechanisms remain uncertain. A range of neuronal and vascular biomarkers was investigated in painful diabetic peripheral neuropathy (painful-DPN) and painless-DPN and used to differentiate painful-DPN from painless-DPN. Skin biopsies were collected from 61 patients with type 2 diabetes (T2D), and 19 healthy volunteers (HV). All subjects underwent detailed clinical and neurophysiological assessments. Based on the neuropathy composite score of the lower limbs [NIS(LL)] plus seven tests, the T2D subjects were subsequently divided into three groups: painful-DPN (n = 23), painless-DPN (n = 19), and No-DPN (n = 19). All subjects underwent punch skin biopsy, and immunohistochemistry used to quantify total intraepidermal nerve fibers (IENF) with protein gene product 9.5 (PGP9.5), regenerating nerve fibers with growth-associated protein 43 (GAP43), peptidergic nerve fibers with calcitonin gene-related peptide (CGRP), and blood vessels with von Willebrand Factor (vWF). The results showed that IENF density was severely decreased (p < 0.001) in both DPN groups, with no differences for PGP9.5, GAP43, CGRP, or GAP43/PGP9.5 ratios. There was a significant increase in blood vessel (vWF) density in painless-DPN and No-DPN groups compared to the HV group, but this was markedly greater in the painful-DPN group, and significantly higher than in the painless-DPN group (p < 0.0001). The ratio of sub-epidermal nerve fiber (SENF) density of CGRP:vWF showed a significant decrease in painful-DPN vs. painless-DPN (p = 0.014). In patients with T2D with advanced DPN, increased dermal vasculature and its ratio to nociceptors may differentiate painful-DPN from painless-DPN. We hypothesized that hypoxia-induced increase of blood vessels, which secrete algogenic substances including nerve growth factor (NGF), may expose their associated nociceptor fibers to a relative excess of algogens, thus leading to painful-DPN.